Biocontrol of Sugarcane Smut Disease by Interference of Fungal Sexual Mating and Hyphal Growth Using a Bacterial Isolate - Liu, Shiyin; Lin, Nuoqiao; Chen, Yumei; Liang, Zhibin; Liao, Lisheng; Lv, Mingfa; Chen, Yufan; Tang, Yingxin; He, Fei; Chen, Shaohua; Zhou, Jianuan; Zhang, Lianhui (Frontiers in Microbiology, 2017)
Sugarcane smut is a fungal disease caused by Sporisorium scitamineum, which can cause severe economic losses in sugarcane industry. The infection depends on the mating of bipolar sporida to form a dikaryon and develops into hyphae to penetrate the meristematic tissue of sugarcane. In this study, we set to isolate bacterial strains capable of blocking the fungal mating and evaluate their potential in control of sugarcane smut disease. A bacterial isolate ST4 from rhizosphere displayed potent inhibitory activity against the mating of S. scitamineum bipolar sporida and was selected for further study. Phylogenetic analyses and biochemical characterization showed that the isolate was most similar to Pseudomonas guariconensis. Methanol extracts from minimum and PDA agar medium, on which strain ST4 has grown, showed strong inhibitory activity on the sexual mating of S. scitamineum sporida, without killing the haploid cells MAT-1 or MAT-2. Further analysis showed that only glucose, but not sucrose, maltose and fructose, could support strain ST4 to produce antagonistic chemicals. Consistent with the above findings, greenhouse trials showed that addition of 2% glucose to the bacterial inoculum significantly increased the strain ST4 biocontrol efficiency against sugarcane smut disease by 77% than the inoculum without glucose. The results from this study depict a new strategy to screen for biocontrol agents for control and prevention of the sugarcane smut disease.